DESIGN OF LIFESTYLE CENTER WITH A NEARLY ZERO ENERGY BUILDING APPROACH IN PEKANBARU - Rafi Ihsan, Muhammad
Indonesia is the fifth-largest emitter of carbon emissions in the world. In Indonesia, carbon emissions are predominantly attributed to land use changes. Carbon emissions are one of the greenhouse gases that can cause detrimental climate changes, such as variations in weather, seasons, and even damage ecosystems. Pekanbaru, as a city with seven new urban planning initiatives, has significant potential for carbon emissions release. Shopping centers, compared to other functions such as hospitals, offices, and hotels, have the highest energy consumption intensity. This underscores the urgency of adopting a sustainable approach in their design and operations. A Lifestyle Center is not just a shopping center, but also a space for social interaction and recreation that can support a sustainable lifestyle. Therefore, the main focus of this design is on the building's operational energy, which is a dominant contributor to the building's life cycle. In implementing the nZEB concept, the goal is not only to improve energy efficiency but also to minimize the carbon generated by its daily operational activities. Thus, this design is expected to contribute to energy efficiency and the reduction of carbon emissions, while also providing new insights and solutions for designing more sustainable shopping centers in the era of urbanization and climate change.